1986
DOI: 10.2527/jas1986.623593x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Monensin in Self-Fed (Salt Limiting) Dry Supplements or on an Alternate-Day Feeding Schedule

Abstract: Two series of trials were conducted to evaluate alternative methods of administering monensin to pasture cattle. In a series of five trials, monensin was incorporated into supplements at 440 mg/kg to provide an average intake of 200 mg X head-1 X d-1 for growing cattle on pasture. Comparisons were made between daily and alternate-day feeding of the supplements. A control treatment consisting of unmedicated supplement fed daily also was included. Monensin at 200 mg/d and 400 mg on alternate days increased gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Cattle (13,410 animals; 247 ± 41 kg BW) were British, Continental or B. indicus breeds. References: Monensin: Bagley et al, 1981;Bagley and Feazel, 1989;Burnham et al, 1997;Cochran et al, 1990;Darden and Wolfrom, 1988;Davenport et al, 1989;Horn et al, 1981;Horn et al, 1988;Keith et al, 1995;Merrill and Stobbs, 1986;Muller et al, 1986;Oliver, 1975;Parrott et al, 1990;Parrott et al, 1986;Potter et al, 1976;Potter et al, 1986;Rossi et al, 1997;Rouquette et al, 1980;Smith et al, 1995;Spears et al, 1989;Utley et al, 1976;Wagner et al, 1984. Lasalocid: Andersen andHorn, 1987;Delcurto et al, 1989;Keith et al, 1995;Paterson et al, 1983;Rode, 1987;Rode et al, 1994;Spears and Harvey, 1984;Thonney et al, 1981;Valdes et al, 1988;Worrell et al, 1990.…”
Section: Methodsmentioning
confidence: 99%
“…Cattle (13,410 animals; 247 ± 41 kg BW) were British, Continental or B. indicus breeds. References: Monensin: Bagley et al, 1981;Bagley and Feazel, 1989;Burnham et al, 1997;Cochran et al, 1990;Darden and Wolfrom, 1988;Davenport et al, 1989;Horn et al, 1981;Horn et al, 1988;Keith et al, 1995;Merrill and Stobbs, 1986;Muller et al, 1986;Oliver, 1975;Parrott et al, 1990;Parrott et al, 1986;Potter et al, 1976;Potter et al, 1986;Rossi et al, 1997;Rouquette et al, 1980;Smith et al, 1995;Spears et al, 1989;Utley et al, 1976;Wagner et al, 1984. Lasalocid: Andersen andHorn, 1987;Delcurto et al, 1989;Keith et al, 1995;Paterson et al, 1983;Rode, 1987;Rode et al, 1994;Spears and Harvey, 1984;Thonney et al, 1981;Valdes et al, 1988;Worrell et al, 1990.…”
Section: Methodsmentioning
confidence: 99%
“…When the amount of monensin increased to 200 mg/day, cattle gained an additional 0.20 lb/day or a 16% improvement compared to cattle not offered an ionophore. Offering supplements containing monensin at 200 or 400 mg/day on alternate days can increase growing calf gain by 0.17 and 0.18 lb/day, respectively (Muller et al 1986). The preceding responses were collected over a variety of pasture forage qualities.…”
Section: Animal Responsementioning
confidence: 99%
“…Despite the benefits of supplementation, an everyday frequency basis for this practice implies higher labour costs (Kunkle et al, 2000) and more complex production system practices. Infrequent supplementation (Moriel et al, 2012) and self-feeding strategies (Muller et al, 1986) are two ways to minimise labour-associated costs. As for infrequent supplementation, Farmer et al (2001) found that even though forage utilisation of dormant tallgrass prairie improved with an increased frequency, no differences were to be expected on animal performance.…”
Section: Introductionmentioning
confidence: 99%
“…As for infrequent supplementation, Farmer et al (2001) found that even though forage utilisation of dormant tallgrass prairie improved with an increased frequency, no differences were to be expected on animal performance. As for self-feeding, these schemes were generally carried out using intake limiters, such as salt (Muller et al, 1986;Riggs et al, 1953). Other chemical intake limiters, such as ammonium chloride, ammonium sulphate or calcium hydroxide (Schauer et al, 2004), were later considered in order to allow ad libitum feeding strategies.…”
Section: Introductionmentioning
confidence: 99%